2004
DOI: 10.1093/molehr/gah016
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tumour necrosis factor- -related apoptosis-inducing ligand and its receptors in the adult human testis

Abstract: Tumour necrosis factor-alpha-related apoptosis-inducing ligand (TRAIL) is a member of the tumour necrosis factor-alpha (TNF-alpha) family of cytokines which is known to induce apoptosis upon binding to its death domain-containing receptors, DR4/TRAIL-R1 and DR5/TRAIL-R2. Two additional TRAIL receptors, DcR1/TRAIL-R3 and DcR2/TRAIL-R4, lack functional death domains and act as decoy receptors for TRAIL. In this study, the presence of TRAIL and its receptors was investigated by immunohistochemistry in adult human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 46 publications
2
30
0
3
Order By: Relevance
“…19 In contrast with the rat testis, TRAIL-R1 was also immunodetected in myoid and Sertoli cells in the human testis. 20 Our immunohistochemical data were similar to those in the Grataroli et al study. 19 We found that, TRAIL-R1 was specifically present in meiotic spermatocytes only in the control testis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…19 In contrast with the rat testis, TRAIL-R1 was also immunodetected in myoid and Sertoli cells in the human testis. 20 Our immunohistochemical data were similar to those in the Grataroli et al study. 19 We found that, TRAIL-R1 was specifically present in meiotic spermatocytes only in the control testis.…”
Section: Discussionsupporting
confidence: 91%
“…There are similar reports, but they do not use testicular rat tissue. Grataroli et al 20 reported the immunolocalization of TRAIL , its receptors and their identification by analyzing proteins and mRNA in human testes. They found that postmeiotic germ cells immuno-expressed both TRAIL and its four receptors, while Leydig cells expressed TRAIL, TRAIL-R2 and TRAIL-R4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a key regulator of SCs differentiation and its over-expression can be associated with an impairment of SCs maturation process, reported as a feature of KS testis [15]. The increased cell death in KS testis can also be explained by the observed over-expression of TNFRSF10B, TNFAIP3, CCNG1, BNIP3 and BNIP3L known to regulate natural testes apoptosis and proliferative capacity of LCs [16][17][18]. Among the down-regulated transcripts we found genes that promote cell cycle progression (BRCA1, BTRC and TRIP13).…”
Section: Testis Cell Death In Ks and Deregulation Of Genes Involved Imentioning
confidence: 99%
“…Among different tissues, it is noteworthy that TRAIL and its receptors are abundantly expressed in human testis (Grataroli et al 2004). Although TRAIL has been proposed to contribute to the control of the number of spermatogonia (Coureuil et al 2010), the physiopathological role of TRAIL in testis remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%